Conquering Freedom and Identity. Encounters and Convergences in Architecture and Music in the Postwar - Clara Germana Gonçalves; Rogério Paulo Vieira de Almeida (Histories of Postwar Architecture)
Architecture and music’s paths in the aftermaths of WWII have been the subject of detailed studies and are well-known in their respective fields.  However, beyond the underlying individual expressions, there has been little work on their parallel paths where common themes, experiences, procedures, shared goals, and achievements are analyzed. In the aftermath of WWII, the idea of progress has faded away, and technology and science are no longer seen as synonymous with progress. Existentialism and the emergence of Social Sciences will be paramount in the new times. If the period between the Wars architecture and music saw an overall longing for universality and order, after 1945 nontraditional approaches, in general, the will for change, and the ideas of freedom and identity associated with those of local, community, individuality, participation, etc., will dominate architecture and music’s new approaches, manifesting in different ways. The text proposes (i) to retrace some key junctures in architectural and musical discourses (both practical and theoretical) emerging in the postwar period, (ii) to explain its relevance in cultural terms and (iii) to evaluate some of its later consequences.  By exposing some parallels between architecture and music disciplines, the present analysis aims to contribute to a better understanding of its contexts and its disciplinary interrelationships.